Konstruksi Tatanan Dasar Politik dalam Islam - Sirojuddin Aly (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2006)
In societal and governmental life, from ancient times to the present, there has been a need for a set of regulations, whether derived directly from religious teachings or through contemporary decisions based on current needs, whether these regulations have been codified in writing or not, whether they are fundamental (constitutional laws) or developments. With these regulations in place, societal and governmental life becomes orderly and organized. Conversely, without a set of regulations, societal life would undoubtedly become chaotic, disorderly, and would inevitably lead to a law of the jungle. In this context, the author attempts to propose some basic principles for the purpose of governing societal and state life from the perspective of Islamic political thought, including the principles of consultation, equality, freedom, upholding justice, and so forth. These principles are indeed universal values, wherein civilized nations in societal and governmental life also apply these principles, albeit with different interpretations and implementations.